Disparitas Penetapan Perwalian Ayah Terhadap Anak Kandung Pada Pengadilan Agama Kota Medan - Herdi, Novantri; Syam, Syafruddin; Tarigan, Tetty Marlina (Jayapangus Press, 2023)
This study to determine the theory of legal certainty and the theory of equality on the disparity in the determination of guardianship of fathers to biological children. This research is library research, using two approaches, documentation (document approach), in the form of status or decision from the Medan City Religious Court, namely Determination Number 109/Pdt.P/2021/PA.Mdn. and Stipulation Number 155/Pdt.P/2021/PA.Mdn. and the case approach. Data collection techniques by means of observation, interviews, and analyzing decisions. The results of the research: 1). The results of the determination of the panel of judges of the Medan City Religious Court against the guardianship of the father of the biological child in the Determination Number 109/Pdt./2021/PA.Mdn., and Number 155/Pdt./2021/PA.Mdn. There are two results of the decision, namely accepted and not accepted. 2). The perception of the judges of the Medan City Religious Court on the disparity in the determination of guardianship of the father to the biological child in Determination Number 109/Pdt./2021/PA.Mdn. and Number 155/Pdt./2021/PA.Mdn. There is no need for a decision from the Religious Courts related to the guardianship of the biological father to the biological child, even if there is a case that is accepted, it needs to be reviewed. 3). A review of certainty theory and equality theory on disparities in the determination of guardianship of fathers to biological children in Determination Number 109/Pdt./2021/PA.Mdn. and Number 155/Pdt./2021/PA.Mdn. There is the presence and disparity of decisions. The two cases assessed have the same substance.